Search for pseudoscalar bosons decaying into e+e− pairs in the NA64 experiment at the CERN SPS - Andreev Yu. M. Yury Mikhaylovich; Banerjee D.; Bernhard J.; Burtsev V. E.; Chumakov A. G. Aleksandr Grigorjevich; Dusaev R. R. Renat Ramilyevich; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich; Trifonov A. Yu. Andrey Yurievich; Vasilishin B. I. Bogdan Ivanovich (2021, 2021)
Title screen